2022
DOI: 10.1186/s12913-022-07657-4
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary development of recommendations for the inclusion of patient-reported outcome measures in clinical quality registries

Abstract: Background Clinical quality registries (CQRs) monitor compliance against optimal practice and provide feedback to the clinical community and wider stakeholder groups. Despite a number of CQRs having incorporated the patient perspective to support the evaluation of healthcare delivery, no recommendations for inclusion of patient-reported outcome measures (PROMs) in CQRs exist. The aim of this study was to develop a core set of recommendations for PROMs inclusion of in CQRs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…However, many studies have suggested that the less-invasive and safe interventional therapy for patients with severe carotid stenosis fails to effectively reduce the recurrence rate and still leaves adverse outcomes in some patients [ 5 , 6 ]. Scholars Ruseckaite et al have found that although stent implantation for the occluded offending vessels causing cerebral infarction can effectively restore blood flow and achieve partial or complete recanalization of vessels, there is a lack of evidence on the long-term effect and stability of this treatment [ 7 ], that is, the impact of interventional therapy on the recurrence rate remains unclear. It is worth noting that stroke is a behavior-related disease, that is, healthy life behaviors are closely related to stroke prevention [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies have suggested that the less-invasive and safe interventional therapy for patients with severe carotid stenosis fails to effectively reduce the recurrence rate and still leaves adverse outcomes in some patients [ 5 , 6 ]. Scholars Ruseckaite et al have found that although stent implantation for the occluded offending vessels causing cerebral infarction can effectively restore blood flow and achieve partial or complete recanalization of vessels, there is a lack of evidence on the long-term effect and stability of this treatment [ 7 ], that is, the impact of interventional therapy on the recurrence rate remains unclear. It is worth noting that stroke is a behavior-related disease, that is, healthy life behaviors are closely related to stroke prevention [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hundreds of PROMs are available for use in the evaluation and screening of pelvic floor disorders and to measure the results of treatment [ 6 ]. PROMs in registries are becoming more widely available and increasingly being used for benchmarking purposes [ 4 , 17 , 18 ]. A number of gynecological surgery registries worldwide capture HRQoL data [ 7 , 19 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Capturing HRQoL data in the APFPR is very important for adding valuable information on safety and effectiveness of mesh-related procedures from a consumer perspective. However, a careful consideration is required for PROMs inclusion in the registry setting [ 4 ]. The length of the instruments and potential time burden should be considered [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…PROMs in registries are becoming more widely available and used for benchmarking purposes [4,16,17].…”
Section: Discussionmentioning
confidence: 99%